Off-axis spectral beam combining of Bragg reflection waveguide photonic crystal diode lasers. (17th May 2018) - Sun, Fangyuan; Wang, Lijie; Zhao, Yufei; Hou, Guanyu; Shu, Shili; Zhang, Jun; Peng, Hangyu; Tian, Sicong; Tong, Cunzhu; Wang, Lijun
Abstract: The spectral beam combining (SBC) of Bragg reflection waveguide photonic crystal (BRW-PC) diode lasers was studied for the first time. An off-axis feedback system was constructed using a stripe mirror and a spatial filter to control beam quality in the external cavity. It was found that the BRW-PC diode lasers with a low divergence and a circular beam provided a simplified and cost-effective SBC. The off-axis feedback broke the beam quality limit of a single element, and an M 2 factor of 3.8 times lower than that of a single emitter in the slow axis was demonstrated.